Housing for Elderly in Nursing Home on the Level of Satisfaction in the work Area of Social Service of Surabaya - Hidayatus Sya’diyah1 , Sukma Ayu Candra Kirana1 , Diyan Mutyah1 , Ayu Citra Mayasari1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
A large number of elderly suffer degenerative brain function decline with the characteristics of progressiveloss of memory function and other cognitive abilities. The number is increasing in almost several. Thepurpose of this study was to look at the effect of housing for the elderly in Nursing Home on the level ofsatisfaction of the elderly in the Social Service area of Surabaya.The research design used was “Pre-Experimental” design. The variable in this study was the interventionvariable that was the housing for the elderly in the Nursing Home and the output variable that was thesatisfaction of the elderly. The population was all the elderly in the work area of the Surabaya Social Service,with the criteria for the age limit of the elderly 60 years and over, with a probability sampling technique. Thestatistical test used was the Wilcoxon Signed Rank Test.The results of the study obtained were divided into before and after the housing. Before the housing treatment,there were 133 respondents (88.6%) who were at good satisfaction level and there were 17 respondents(11.4%) who were at very good satisfaction levels. After the housing treatment, the results showed that therewere 107 respondents (71.3%) who were at good satisfaction level and there were 43 respondents (28.7%)who were at very good satisfaction level. in addition, the results of the Wilcoxon sign rank statistical test was0.00. It indicated that there was an effect of housing for the elderly on their level of satisfaction.